2015
DOI: 10.1093/cje/bev016
|View full text |Cite
|
Sign up to set email alerts
|

Inequality, the Great Recession and slow recovery

Abstract: Rising inequality reduced income growth for the bottom 95 percent of the US personal income distribution beginning about 1980. To maintain stable debt to income, this group's consumption-income ratio needed to decline, which did not happen through 2006, and its debt-income ratio rose dramatically, unlike the ratio for the top 5 percent. In the Great Recession, the consumption-income ratio for the bottom 95 percent did finally decline, consistent with tighter borrowing constraints, while the top 5 percent ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(79 citation statements)
references
References 59 publications
(39 reference statements)
3
67
0
Order By: Relevance
“…We advocate changing the EU's wage-moderation strategy. We confirm the central idea in the post-Keynesian/post-Kaleckian demand-led model developed by Bhaduri and Marglin (1990), which argues that high real wages generate high effective demand, against the view that high labor costs discourage production (Lavoie and Stockhammer 2012, Onaran and Galanis 2012, Cynamon and Fazzari 2015.…”
Section: Introductionsupporting
confidence: 86%
“…We advocate changing the EU's wage-moderation strategy. We confirm the central idea in the post-Keynesian/post-Kaleckian demand-led model developed by Bhaduri and Marglin (1990), which argues that high real wages generate high effective demand, against the view that high labor costs discourage production (Lavoie and Stockhammer 2012, Onaran and Galanis 2012, Cynamon and Fazzari 2015.…”
Section: Introductionsupporting
confidence: 86%
“…If we agree with the idea that the evolution of the propensity to save of rentiers prevails over the evolution of the propensity to save of modest households, from our point of view, we have to explore the possibility that recessions first provoke a decrease in the propensity to save (consumption smoothing) and then an increase so as to return to normal conditions. Some empirical studies seem to confirm this kind of behaviour as shown by Cynamon and Fazzari (2013) when they examine the rise of inequalities 3 [E]ssentially all of the increased spending apparent in the aggregate data (the acceleration in the saving rate's decline shown in figure 1) can be attributed to an increase in the propensity to consume out of income undertaken by the richest households in the U.S. (Maki and Palumbo, 2001, p. 3).…”
mentioning
confidence: 88%
“…However, this result does not hold if we consider an endogenous capitalists' propensity to save evolving with the state of the economy as captured by the rate of capacity. Following the stylized facts discussed in Cynamon and Fazzari (2013) and the discussion in section 3, we assume that rentiers' propensity to save varies in the short-run according to the following simple linear relation:…”
Section: A Post-keynesian Macroeconomic Model With a Partially Endogementioning
confidence: 99%
“…Cynamon and Fazzari (2014) come to a similar conclusion about debt and spending across the income distribution, using a combination of micro and macro data sources.5 Bertrand and Morse (2013) andBricker, Ramcharan and Krimmel (2014) describe other (non-standard) mechanisms by which rising inequality may increase aggregate spending.…”
mentioning
confidence: 86%